THE END OF CHINA’S ONE-CHILD POLICY AND THE IMPLEMENTATION OF CHINA’S TWO-CHILD POLICY 2015-2016 AS RESPONSE TO THE INTERNATIONAL PRESSURE - Baiq Fatin Islami (HI 16 UMY 151, 2016)
*151 The Chinese government has recently changed the one-child policy becoming two-child policy. The new policy allows all Chinese couple to have two children. This approach has been taken since the reign of the Communist Party under the leadership of Xi Jinping. Considering that the one-child policy will bring fatal effects for China and its relationship with other countries. The purpose of this study is intended to determine the factors behind the decision-making that encourages the Chinese government to change the family planning policy. This study is based on collected information since the beginning of the Xi Jinping administration in 2010-2016 and supporting information from previous years. Chinese government decision-making will be analyzed using the theory of Graham T. Allison about decision-making policy by rational actors. According to Allison, rational actors are required to take rational decisions based on the national interests, alternative or options, and consider the consequences. The main results showed that the most influential factors in the decision of the Chinese government to change the one-child policy are internal and external factors. Internal or domestic factors, the existence of demographic and economic instability. External or international factors, the criticism from international actors related with the implementation of China's family planning policy which violated human rights.